Penerapan Nilai-Nilai Kosmopolitanisme Islam Dalam Mencegah Radikalisme Agama Pada Masyarakat Muslim Plateau Dieng - Angga Teguh Prastyo (POROS ONIM: Jurnal Sosial Keagamaan, 2022)
Islamic cosmopolitanism contributes to strengthening the foundation of diversity in the midst of ethnic differences and cultural territorial boundaries in Indonesia. Religious and cultural relations are often seen as triggers for protracted diversity conflicts. This view is built because of the absence of awareness and social harmony inherent in a pluralistic society. This paper expands the study of Islamic cosmopolitanism in Indonesia in building social diversity in a pluralistic society. The research method uses descriptive qualitative. Data collection techniques using interviews, documentation and observation. Meanwhile, data analysis uses flow stages: data reduction, data display, and conclusion verification. This study concludes that the values ​​of Islamic cosmopolitanism in the Muslim community of Plateau Dieng are built from the values ​​of religious awareness and social harmony that are rooted in and become an inherent part of the collective identity of the community. This confirms that the values ​​of Islamic cosmopolitanism can develop and become an inseparable part of the collective identity of a pluralistic society.